KEPEMIMPINAN MANAJERIAL KEPALA SEKOLAH DI SMP NEGERI I BANDAR LAMPUNG - Fransiska Olivia Dewanti; Bujang Rahman; Sowiyah Sowiyah (9 772338317006)
The purpose of this study to analyze the managerial leadership of the principal. This research is a qualitative approach with a phenomenological approach, the research informants Principal Deputy Principal consisting of Vice Principal of Curriculum, Vice Principal of Facilities and Infrastructure, Vice Principal of Student Affairs, Vice Principal of Quality Management and Public Relations. The data collection is done by observation, interviews, and documentation. Data analysis using data reduction, results of this study demonstrate managerial ability principals in realizing quality school management. The concept of skills possessed by principals namely: understanding the complexity of the management of school organization, the ability to make decisions at the level of school education, and the ability to create a mapping school organization. Human relations skills possessed by the principal, skill in building cooperation with schools, teachers' skills in motivating performance, skill in organizing elements of internal school education, and skills in organizing external elements of the school education. Tujuan penelitian ini untuk menganalisis kepemimpinan manajerial kepala sekolah.Penelitianinimerupakan penelitian pendekatan kualitatif dengan pendekatan fenomenologi, informan penelitian Kepala Sekolah para Wakil Kepala Sekolah yang terdiri dari Wakil Kepala Sekolah Bidang Kurikulum, Wakil Kepala Sekolah Bidang Sarana Dan Prasarana, Wakil Kepala Sekolah Bidang Kesiswaan, Wakil Kepala Sekolah Bidang Manajemen Mutu dan Humas. Pengumpulandatadilakukandengan observasi, wawancara, dan dokumentasi.Analisis data menggunakan reduksi data. Hasil penelitian ini menunjukkan kemampuan manajerial kepala sekolah dalam mewujudkan pengelolaan sekolah yang bermutu. KeterampilanKonsep yang dimiliki oleh kepala sekolah yakni: memahami komplek sitas pengelolaan organisasi sekolah, kemampuan dalam membuat keputusan pendidikan pada level sekolah, dan kemampuan dalam membuat pemetaan organisasi sekolah. Keterampilan hubungan antar manusia dimiliki oleh kepala sekolah, keterampilan dalam membangun kerjasama dengan sekolah, keterampilan dalam memotivasi kinerja guru, keterampilan dalam mengorganisasikan elemen-elemen pendidikan intern sekolah, dan ekstern sekolah.Kata kunci: kepemimpinan manajerial kepala sekolah, mutu